Situation Report: Hungary, 25 January 1977 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Thirty-Four Intellectuals Express Solidarity with Character 77 Changes in Sickness Benefits New Regulations on Sale of Medicines New Play Implies Rejection of Party Ideology Increased Effort Required to Fulfill 1977 Agricultural Plan Hungary's Indebtedness to the Nonsocialist World